Applied mechatronics and mechanics : system integration and design - Singh, Satya Bir; Ranjan, Prabhat; Haghi, A. K. (Palm Bay, FL, USA ; Burlington, ON, Canada : Apple Academic Press ; Boca Raton, FL, USA ; Abingdon, Oxon, UK : CRC Press, 2021)
"This research-oriented book, Applied Mechatronics and Mechanics: System Integration and Design, presents a clear and comprehensive introduction to applied mechatronics and mechanics. It presents some of the latest research and technical notes in the field of mechatronics and focuses on the application considerations and relevant practical issues that arise in the selection and design of mechatronics components and systems as well. In the field of mechatronics and mechanics, the variety of materials and their properties is reflected by the concepts and techniques needed to understand them: a rich mixture of mathematics, physics, and experiment. These are all combined in this informative book, based on the chapter authors' years of experience in research and teaching. With the inclusion of several case studies, this valuable volume will enable readers to comprehend and design mechatronic systems by providing a frame of understanding to develop a truly interdisciplinary and integrated approach to engineering. It will be helpful to faculty and advanced students as well as specialists from all pertinent disciplines."--
Dynamic Balancing of Planar Mechanisms Using Nondominated Sorting Jaya Algorithm / Prem Singh, Ramanpreet Singh, and Himanshu Chaudhary -- Vibration Control of a Car Suspension System Usinga Magnetorheological Damper with a Fuzzy-Logic Controller / G. Pohit -- A Review of the Application of Mechatronics in Manufacturing Processes / T. Muthuramalingam -- Application of a Nature-Inspired Algorithm in Odor Source Localization / Kumar Gaurav, Ramanpreet Singh, Ajay Kumar, and Ram Dayal -- Tire Pressure Monitoring Systems: A Case Study in Automotive Mechatronics / Narayan Kumar and B. Ravindra -- A Retrospective Assessment of Elastic-Plastic and Creep Deformation Behavior in Structural Components Like Discs, Cylinders, and Shells / Shivdev Shahi, Satya Bir Singh, and A.K. Haghi -- Investigation of Elastic-Plastic Transitional Stresses in Zirconia-Based Ceramic Dental Implants under Uniaxial Compression / Shivdev Shahi, Satya Bir Singh, and A.K. Haghi -- Recent Developments in the Theory of Nonlocality in Elastic and Thermoelastic Mediums / Sukhveer Singh, Parveen Lata, and Satya Bir Singh -- Investigation of Creep Performance of an Isotropic Composite Disc under Thermal Gradients / Vandana Gupta and Satya Bir Singh -- Application of a Fractional-Order PID Controller to an Underactuated System / Tung-Yung Huang and Shih-Ying Hung -- Evaluating the Effect of an Amputee's Physical Parameters of Pressure on a Lower-Limb Prosthetic Socket Using a Fuzzy-Logic-Based Model / Vimal Kumar Pathak, Chitresh Nayak, and Deepak Rajendra Unune -- Experimental Investigation and Optimization of Process Parameters in Oblique Machining Process for Hard-to-Cut Materials Using Coated Inserts / Purnank Bhatt, Mihir Solanki, Anand Joshi, and Vijay Chaudhari -- Mechanical Design of a Slider-Crank Mechanism for a Knee Orthotic Device Using the Jaya Algorithm / Ramanpreet Singh and Vimal Kumar Pathak.
OCLC-licensed vendor bibliographic record.
Keywords: Mechatronics; Mechanics, Applied; SCIENCE / General; SCIENCE / Mechanics / General; TECHNOLOGY / Electronics / General